Evaluating sago palm (Metroxylon sagu Rottb.) photosynthetic performance in waterlogged conditions: utilizing pulse-amplitude-modulated (PAM) fluorometry as a waterlogging stress indicator - A. Azhar; D. Makihara; H. Naito; H. Ehara (Journal of the Saudi Society of Agricultural Sciences)
Photosynthetic performance of sago palm (Metroxylon sagu Rottb.) was evaluated in normal and waterlogged conditions. Net assimilation rate (AN), light response curve of net assimilation rate (AN/I) and pulse-amplitude modulation fluorescence vs. irradiance (PAM/I), leaf water potential, leaf chlorophyll content and leaflet area were measured. AN was higher in a particular period of waterlogging than in the normal condition. However, prolonged waterlogging (more than two months) negatively affected sago palm photosynthetic capacity. This was indicated by reduction in several photosynthetic parameters such as AN, maximum value of AN obtained at maximum irradiance (AN (Imax)), quantum yield at zero to 200 µmol m−2 s−1 irradiance (ϕ(Io_I200)), asymptotic photosynthetic efficiency (αo), and maximum electron transport rate (ETRmax). The plants experiencing waterlogging produced high qNmax and NPQmax values. Prolonged waterlogging period also caused significant reduction in leaf water potential (ψleaf) and photosynthetic pigments content. Normal soil conditions with a sufficient amount of water are preferable in order for the plant to generate higher photosynthetic capacity and facilitate stable sago production. Keywords: Light response curve, Metroxylon sagu Rottb, Net assimilation rate, Pulse-amplitude modulated (PAM) fluorometry